The Characteristics of Kampung Sekayu Conservation Area, Semarang City - Agnies Ayu Kusumaningdyah; Adhista Putri Presilia; Anindya Putri Tamara; Erliza Syahrani (Sinektika: Jurnal Arsitektur, 2022)
Kampung Sekayu is an original village in Semarang City which has a cultural heritage building in its area, so its existence needs to be maintained. Its strategic location in the center of the city makes this village develop into a trade and service area, thus affecting the area’s physical characteristics. Character identification is needed to know the current condition of the area. The method used in this research is descriptive qualitative and explanatory techniques. This study shows that the physical condition of the building has partially changed due to the development of the area from a residential area to a trade and service area. However, some buildings can still maintain their distinctive character as the original buildings that were built during the colonial era. The Great Mosque as a landmark of this area is a characteristic that cannot be separated from the existence of this village. Judging from the social characteristics of the community, cultural mixing occurs because the composition of residents is now dominated by immigrants